Ground State Electron Energies in sp3 Hybridized Si and C atoms in C-terminated 4H-SiC - Chanana, Ravi Kumar (European Journal of Applied Sciences, 2023)
In this research article, the ground state potential energies of the interacting Si and C atom electrons of the sp3 hybridized C-terminated 4H-SiC are calculated. The Si and C atoms are bonded tetrahedrally in 4H-SiC. The ground state potential energies for the interacting Si and C atom electrons in the C-terminated 4H-SiC are found to be -0.4163 eV and -0.9528 eV respectively.